To simplify \( 2^4 \cdot 2^2 \), we can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
So, we add the exponents:
\[ 2^4 \cdot 2^2 = 2^{4+2} = 2^6 \]
Thus, the simplified expression is:
\[ \boxed{2^6} \]
2, to the power 4 , dot, 2, squared
1 answer
To simplify \( 2^4 \cdot 2^2 \), we can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
So, we add the exponents:
\[ 2^4 \cdot 2^2 = 2^{4+2} = 2^6 \]
Thus, the simplified expression is:
\[ \boxed{2^6} \]